Presentation and outcome of severe anticholinesterase insecticide poisoning. Issue 5 (1st May 2002) - Verhulst, L; Waggie, Z; Hatherill, M; Reynolds, L; Argent, A
Abstract : Aims: To document the patterns of presentation and outcome of severe anticholinesterase insecticide poisoning in children requiring intensive care. Methods: Retrospective case note review of all 5541 children admitted to the paediatric intensive care unit (PICU) of a university hospital during the 10 years from January 1990 to May 2000. Fifty four children (1%) with anticholinesterase insecticide poisoning were identified. Presenting features, route of exposure, treatment, complications, and mortality were recorded. Data were analysed by the Fisher's exact and Mann–Whitney tests. Results: More children than expected were from a rural area (46% versus 25%). Decontamination occurred in 50% of children prior to PICU admission. Enteral exposure was most common (n = 27; 50%). Median pseudocholinesterase level was 185 IU/l (range 75–7404). Median total dose of atropine required to maintain mydriasis was 0.3 mg/kg (range 0.03–16.7) over a median of 10 hours (range 1–160). Complications included coma (31%), seizures (30%), shock (9%), arrhythmias (9%), and respiratory failure requiring ventilation (35%). No significant differences were detected in incidence of seizures, cardiac arrhythmias, respiratory failure, mortality, duration of ventilation, or PICU stay, according to route of exposure, or state of decontamination. Four children died (7%). Mortality was associated with the presence of a cardiac arrhythmia (likelihood ratio 8.3) and respiratory failure (likelihood ratio 3.3). Conclusion: The mortality and morbidity of severe anticholinesterase insecticide poisoning in childhood is not related to route of exposure, or to delay in decontamination. However, the presence of either a cardiac arrhythmia or respiratory failure is associated with a poor prognosis.